Glutamate Dehydrogenase Is Important for Ammonia Fixation and Amino Acid Homeostasis in Brain During Hyperammonemia - Voss, Caroline M.; Arildsen, Lene; Nissen, Jakob D.; Waagepetersen, Helle S.; Schousboe, Arne; Maechler, Pierre; Ott, Peter; Vilstrup, Hendrik; Walls, Anne B. (Frontiers in Neuroscience, 2021)
Impaired liver function may lead to hyperammonemia and risk for hepatic encephalopathy. In brain, detoxification of ammonia is mediated mainly by glutamine synthetase (GS) in astrocytes. This requires a continuous de novo synthesis of glutamate, likely involving the action of both pyruvate carboxylase (PC) and glutamate dehydrogenase (GDH). An increased PC activity upon ammonia exposure and the importance of PC activity for glutamine synthesis has previously been demonstrated while the importance of GDH for generation of glutamate as precursor for glutamine synthesis has received little attention. We therefore investigated the functional importance of GDH for brain metabolism during hyperammonemia. To this end, brain slices were acutely isolated from transgenic CNS-specific GDH null or litter mate control mice and incubated in aCSF containing [U-13C]glucose in the absence or presence of 1 or 5 mM ammonia. In another set of experiments, brain slices were incubated in aCSF containing 1 or 5 mM 15N-labeled NH4Cl and 5 mM unlabeled glucose. Tissue extracts were analyzed for isotopic labeling in metabolites and for total amounts of amino acids. As a novel finding, we reveal a central importance of GDH function for cerebral ammonia fixation and as a prerequisite for de novo synthesis of glutamate and glutamine during hyperammonemia. Moreover, we demonstrated an important role of the concerted action of GDH and alanine aminotransferase in hyperammonemia; the products alanine and alpha-ketoglutarate serve as an ammonia sink and as a substrate for ammonia fixation via GDH, respectively. The role of this mechanism in human hyperammonemic states remains to be studied.